Systemic drug therapy for neuropathic pain - Lilian Hennemann-Krause; Sidney Sredni (Revista Dor)
ABSTRACT BACKGROUND AND OBJECTIVES: Neuropathic pain involves different etiologies, syndromes, pathophysiologic mechanisms and clinical symptoms, in addition to different treatment modalities. Most commonly used drugs to control neuropathic pain are antidepressants, anticonvulsants and opioids, and even so, they have moderate efficacy, with 50% pain relief in less than one third of patients. This study aimed at developing a guiding protocol for pharmacologic neuropathic pain management and also at introducing other drugs which may also relieve neuropathic pain. CONTENTS: This study has evaluated updated protocols of the Canadian Pain Society, the International Association for the Study of Pain, the European Federation of Neurological Societies and relevant references, being developed an algorithm for systemic drug therapy for neuropathic pain, made up of first line medications (tricyclic antidepressants, gabapentinoids and serotonin and norepinephrine reuptake inhibitors), second line medications (weak and strong opioids) and third line medications (selective serotonin reuptake inhibitors, dopamine and norepinephrine reuptake inhibitors and other anticonvulsants). Other drugs (anti-inflammatory, steroids and baclofen) and venous drug therapy (lidocaine and ketamine) used to control pain were also addressed. Major pharmacological actions, titration, interactions and relevant adverse effects of drugs indicated in the study were highlighted. CONCLUSION: Ideally, initial screening for pain control should be done with single therapy. If needed, other drugs may be combined to reach different pathophysiologic mechanisms and better neuropathic pain control. The algorithm should be a guide for analgesia, treatment should be tailored and, when indicated, combined with topic therapy and other non-pharmacological approaches.